On Strong $(i,j)$-Semi$^{*}$-$\Gamma $-Open Sets in Ideal Bitopological Space - Bukhatwa, Ibtissam; Demiralp, Sibel (Gaziosmanpasa University, 2024)
In this study, we introduce the concepts of $(i,j)$-semi$^{*}$-$\Gamma $-open sets within the context of ideal bitopological spaces. This concept is demonstrated to be weaker than the established the notion of $(i,j)$-semi-$\Gamma $-open sets. Subsequently, we define strong $(i,j)$-semi$^{*}$-$\Gamma $-open sets in ideal bitopological spaces, elucidating some of their essential characteristics. Furthermore, leveraging this newly introduced concept, we establish the notions of strong $(i,j)$-semi$^{*}$-$\Gamma $-interior and strong $(i,j)$-semi$^{*}$-$\Gamma $-closure.
Keywords: Topoloji; j)$-semi$^{*}$-$\gamma $-open sets; ideal bitopological spaces; j)$-$\gamma $-open sets; QA1-939; $(i; generalized open sets; Ideal bitopological spaces; generalized open sets; $(i; j)$-$\Gamma $-open sets; j)$-semi$^{*}$-$\Gamma $-open sets; Topology; Mathematics